Evaluation of Entrepreneurial Opportunities - Laboutka, Tomáš; Lukeš, Martin, 1976-; Fried, Jan; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2009)
The overall aim of this study is to provide insights into the process of entrepreneurial opportunity evaluation, as it is really exercised by successful entrepreneurs. First part addresses the theoretical background of the problem and provides a comprehensive overview of the existing literature. Six propositions for the construct of entrepreneurial opportunity evaluation theory are designed. Second part focuses on empirical testing and analysing of the six propositions. The research is based on personal interviews with 31 highly-experienced entrepreneurs in the Czech Republic. Practical suggestions are provided for academics, and 10 main recommendations are presented for the entrepreneurs.
Vedoucí práce: Martin Lukeš
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2010
Rok obhajoby 2010
Keywords: international Management [obor dipl. práce]; diplomové práce; master's theses